Kajian Potensi Energi Baru Terbarukan Untuk Mendukung Transisi Energi di Kota Samarinda - Putri, Resty Intan; Alham, Nur; Larasati, Tantra; Ananta Fathurrozi; Respati, Lucia (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The dependence on the use of non-renewable fossil energy in society certainly causes various problems, one of which is environmental problems in the form of increased carbon emissions. Fossil energy will also be increasingly limited in the future due to increased energy use, so a transition to new renewable energy is needed. Indonesia has considerable potential in New Renewable Energy, but the utilization and understanding of New Renewable Energy among the public remain low. The renewable energy was only 13,09% in 2023. This is due to Indonesia’s continued focus on fossil energy. Through this Service Program, it aims to socialize the potential and utilization of New Renewable Energy in Indonesia, especially in the samarinda area. The stages of this program include discussion and socialization of the potential amount of New Renewable Energy in Samarinda that can be utilized for energy needs among the community. This program provides understanding and awareness to the public about the importance of transitioning to New Renewable Energy and creating a commitment between the city government and the community regarding the transition to New Renewable Energy. This activity is expected to be the beginning of a change in the use of energy sources to create more environmentally friendly environmental conditions.